Abbie Downes: capstone - Downes, Abbie, artist (Colorado State University. Libraries, 2015)
The artist's statement: Within this body of work I aim to touch on the idea of anonymity: the lack of individual features. I express this idea quite literally with the removal of facial features from my models. Yet, each of them is like a book, complex with their own unique story. We are told as children to never judge a book by its cover, yet as time goes on that idea seems to wear off. My work deals with the trouble we all face when it comes to relating to others and the initial stages of all relationships we form throughout our lives.
Books
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.